Species identification of strains belonging to genus Citrobacter using the biochemical method and MALDI-TOF mass spectrometry - Kolínská, Renáta; Spanělová, Petra; Dřevínek, Michal; Hrabák, Jaroslav; Zemličková, Helena (Folia microbiologica, 2015)
Strains of genus Citrobacter (152 isolates from 1950 to 1988 deposited in the Czech National Collection of Type Cultures, Prague) were re-classified using biological and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) methods. One-hundred thirty-six strains (ca. 90 %) were identified to the species level using the biological method with evaluation by Farmer matrix. MALDI-TOF MS exhibited better identification capability, the data being more compact; the method was unambiguously successful in typing 145 (95 %) strains. Comparison of the results of identification by the two methods revealed differences (for 12 samples) in identified species which, considering all biochemical and/or MS characteristics, could be attributed to the natural variability of strains and close relation of the misidentified species (all of them belonged to the Citrobacter freundii complex). Taking into account all the above data, both methods can be considered reliable; however, the MALDI-TOF MS exhibits higher accuracy, efficiency, and rapidity.
Keywords: Bacterial Typing Techniques; biochemie; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Biochemistry; techniky typizace bakterií; Citrobacter